Broadband Printed Cross-Dipole Element with Four Polarization Reconfigurations for Mobile Base Station Array Antenna Applications - Soon-Young Eom; Ic-Pyo Hong; Jong-Myeon Kim (International Journal of Antennas and Propagation)
This paper describes a broadband printed cross-dipole element with four polarization reconfigurations (BPCDE_PR). The BPCDE_PR can configure two linear and two circular polarizations in the operating band of 1.7–2.5 GHz. To implement the broadband polarization reconfigurations, switched network type broadband phase shifters are proposed and designed. The fabricated BPCDE_PR prototype with switched network including broadband phase shifters shows good electrical performances and the desired polarization reconfigurable functions in the operating band.